IT STRATEGY FOR AN SME IN ANIMAL HEALTHCARE - Deivasigamani, Dhayanand (2010)
Irrespective of the employee strength and volume of business, today’s business houses have started utilizing latest technologies in meeting their IT requirements. Majority of the organization in the complex and dynamic business environment have become completely dependent on IT systems and now there arise a situation in which without IT, businesses cannot run. Beyond using it for day to day activities of the business, for competing successfully in the market place, companies have started using IT as a tool of competitive advantage. Such a strategic use of Information Technology/Information Systems (IS/IT) paves way for further analysis on the relationship between strategy from the business side and IT side of the organization. The concept of Strategic Alignment deals with the issue of identifying and reducing the gap that exists between the two important entities of the organizations. In this dissertation I have tried to identify necessary concepts and use them in order to address issues faced by a leading animal healthcare organization in the United Kingdom.